2004
DOI: 10.1001/archinte.164.14.1552
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trials of Vitamin E in the Treatment and Prevention of Cardiovascular Disease

Abstract: The ORs and CIs provide strong support for a lack of statistically significant or clinically important effects of vitamin E on cardiovascular disease. The use of agents of proven lack of benefit, especially those easily available over the counter, may contribute to underuse of agents of proven benefit and failure to adopt healthy lifestyles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(68 citation statements)
references
References 34 publications
1
62
0
2
Order By: Relevance
“…Vitamin E supplementation does not prevent vascular events [297]. Fat-soluble antioxidant supplements may increase mortality [298].…”
Section: Secondary Preventionmentioning
confidence: 99%
“…Vitamin E supplementation does not prevent vascular events [297]. Fat-soluble antioxidant supplements may increase mortality [298].…”
Section: Secondary Preventionmentioning
confidence: 99%
“…Epidemiologic evidence has linked the intake of vitamin E to reduced risk of CHD, but results from randomized clinical trials have been largely negative [29]. Several clinical trials have also ruled out that high-dose supplementation with beta-carotene or folic acid reduces risk of cardiovascular events.…”
Section: Antioxidantsmentioning
confidence: 99%
“…There is no published evidence of increased mortality in children using VE therapy. Furthermore, three other meta-analyses found no evidence that VE supplementation up to 800 IU/day significantly increased or decreased CVD mortality or allcause mortality [145][146][147].…”
Section: Evidence Of Vitamin E Safetymentioning
confidence: 98%
“…Generally, vitamin E is well tolerated, and many studies have reported no increased mortality [145][146][147][148][149][150][151]. The Deprenyl and Tocopherol Antioxidative Therapy for Parkinson's Disease (DATATOP) study used mega-doses of VE (2,000 IU/day) and did not reveal increased mortality over 13 years of observation [148].…”
Section: Evidence Of Vitamin E Safetymentioning
confidence: 99%